Refeeding with Free Lactose Milk ( A1 - 110 Nestle) in Children Suffering from Gastroenteritis and Dehydration - Suharjono Suharjono; Sunoto Sunoto; Aswitha Boediarso; Hentyanto Hendardji; Soegiharto Soegiharto (Indonesian Pediatric Society, 1975)
Forty one infants suffering from diarrhoea hospitalized in the Department of Child Health, Medical School, University of lndonesia/Dr. Tjipto Mangunkusumo General Hospital, Jakarta, from August 15, 1973 to January 15, 1974 were refed with